The Relevance of Conventional Reference Services in the Digital Age: A Case Study of the Library of Univeristas Perintis Indonesia - Satria, Andra Tri; Sari, Riska Amelia; Khairatih, Rizka; Hasibuan, Suci Annisa; Saputra, Zakaria; Rahmi, Lailatur (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2025)
In the midst of the rapid development of information technology, libraries are required to transform in providing information services. However, conventional services based on printed collections still have an important role, especially in supporting specific and in-depth reference needs. This study aims to examine the existence and relevance of conventional reference services that are still organized at the Library of Universitas Perintis Indonesia. The method used was qualitative research with a field study approach through direct observation and interviews with reference librarians. The results showed that printed collections such as dictionaries, encyclopedias, and directories are still actively used, especially by final year students and lecturers who need valid references in scientific writing. The main challenges faced are the limited budget for collection renewal and the lack of user understanding of the benefits of printed collections. However, these services have the opportunity to continue to be relevant if integrated with digital approaches and the promotion of information literacy. This research confirms that conventional services do not lose relevance, but need to be adapted to the dynamics of user needs in the digital era.